Valence and conduction band offsets for sputtered AZO and ITO on (010) (Al0.14Ga0.86)2O3. (10th January 2019) - Fares, Chaker; Ren, F; Lambers, Eric; Hays, David C; Gila, B P; Pearton, S J
Abstract: (Al x Ga1− x )2 O3 /Ga2 O3 metal-oxide semiconductor field effect transistors are emerging as candidates for rf and power electronics, but a drawback is the high contact resistances on these wide bandgap semiconductors. A potential solution is to use narrower gap transparent conducting oxides such as IZO and ATO to reduce the interfacial resistance. In this paper, we report the measurement of the valence band offset of the AZO/(Al0.14 Ga0.86 )2 O3 and ITO/(Al0.14 Ga0.86 )2 O3 heterointerfaces using x-ray Photoelectron Spectroscopy. The single-crystal β -(Al0.14 Ga0.86 )2 O3 was grown by molecular beam epitaxy. The bandgaps of the sputter-deposited AZO and ITO were determined by reflection electron energy loss spectroscopy to be 3.2 ± 0.20 and 3.5 ± 0.20 eV, respectively, while high resolution XPS data of the O 1s peak and onset of elastic losses was used to establish the (Al0.14 Ga0.86 )2 O3 bandgap as 5.0 ± 0.30 eV. The valence band offsets were −0.59 eV ± 0.10 eV and −1.18 ± 0.20 eV, respectively, for AZO and ITO. The conduction band offsets were 1.21 ± 0.25 eV for AZO, and 0.32 ± 0.05 eV for ITO. Both were of the straddling gap, type I alignment on β -(Al0.14 Ga0.86 )2 O3 and all the offsets are negative, consistent with achieving improved electron transport across the heterointerface.